The Potential of Probiotics from Fermented Rice Water on Fibroblast Proliferation and Migration: A Systematic Review - Nury Nur Melati Tanjung; Dian Widiyanti; Indra Kusuma; Dicky Budiman (GLOBAL HEALTH SCIENCE GROUP, 2026)
Fermented rice water (FRW) has been traditionally used for skin care, but its biological mechanisms on fibroblasts, key cells in wound healing, have not been fully characterized. This systematic review aims to evaluate the efficacy of FRW on fibroblast proliferation and migration and to identify the molecular pathways involved. A literature search was conducted through PubMed, Scopus, and Google Scholar using the keywords